Nilai-Nilai Syariah Dalam Proses Penawaran: Kajian Literatur Atas Prinsip Transparansi Dan Kejujuran - Hairullah Efendi; Mohd Winario (EL-EMIR Institute, 2026)
This study aims to examine sharia values in the offering process with a focus on the principles of transparency and honesty through a literature review approach. In the perspective of Islamic economics, the offering process is not merely understood as an economic activity, but also as a form of moral responsibility that must be aligned with Islamic values. Transparency requires the disclosure of information related to product quality, pricing, and conditions, while honesty emphasizes the integrity of business actors in every transaction. These two principles serve as fundamental foundations in preventing practices such as gharar, tadlis, and fraud in muamalah. In the context of the digital era, the implementation of transparency and honesty faces new challenges due to the rapid growth of online transactions and e-commerce, thereby requiring stronger ethical commitments from business actors. The findings indicate that consistent application of sharia values has a positive impact on enhancing consumer trust and loyalty. Furthermore, transparency and honesty play a crucial role in ensuring business sustainability by building reputation, credibility, and long-term competitive advantage. Thus, sharia values in the offering process are not only normatively relevant but also strategically important in supporting the development of a just and sustainable Islamic economy.